A technical note on the assessment of human sperm vitality using eosin–nigrosin staining. Issue 6 (June 2020) - Mortimer, David
Abstract: Research question: How many spermatozoa and slides need to be counted to make a reliable assessment of sperm vitality? Currently, various authorities recommend assessing human sperm vitality on counts of at least 200 cells, but on one or two slides. Design: This was an observational study on duplicate eosin–nigrosin stained sperm vitality slides made from 58 ejaculates. Assessments were made using counts of 2 × 100 and 1 × 200 cells per slide, all performed by the same trained expert observer. Results: Although assessments tend to show fewer and smaller outlier values when based on counts of 200 spermatozoa than 100, and on 2 × 200 than 1 × 200, counting 200 spermatozoa from one slide provides a result with sufficient accuracy for the clinical purpose of ascertaining whether the immotile spermatozoa in an ejaculate showing low sperm motility are alive or dead. Conclusions: While the increased accuracy of results derived from counts of 2 × 200 cells might be important in research studies where sperm vitality is the specific end-point of interest, counting at least 200 spermatozoa from one smear is sufficiently accurate for the clinical purpose of establishing whether the immotile spermatozoa seen in ejaculates with low sperm motility are alive or not. Consequently, the extra workload of performing replicate counts and the associated calculations does not increase the clinical value of the result, and hence is unnecessary in routine semen analysis. Careful laboratory technique as well as proper staff training and competence are essential. The conclusions might not be applicable to staining methods other than the recommended one-step eosin–nigrosin technique.